Clinicopathologic and immunophenotypic features in dogs with presumptive large granular lymphocyte leukaemia. Issue 11 (12th August 2022) - Jaensch, SM; Hayward, DA; Boyd, SP
Abstract : Large granular lymphocytic leukaemia (LGLL) has been described in a range of species but has been most commonly reported in humans and dogs. In both species, this neoplasia exhibits diversity in both phenotype and biological behaviour with phenotype only partially predicting behaviour. There is currently little knowledge of concurrent haematological and serum biochemistry features or concurrent occurrence of distinct neoplasia in canine LGLL cases. This study presents a canine case series and defines haematological parameters, novel serum biochemistry findings and phenotype of the large granular lymphocytes in an Australian case series. Neutrophilia was the most common haematological abnormality, identified in 43% of dogs, and 84% of dogs with biochemistry data available had elevated serum gamma‐glutamyl transferase. Five of the 40 dogs in this study exhibited concurrent neoplasia during the period of the study, demonstrating this is a relatively common clinical outcome in canine LGLL cases. In agreement with previous canine and human studies, the most common LGLL phenotype in dogs is CD3+, CD4− and CD8+. Further work is needed to define the variables predictive of the biological behaviour of LGLL in dogs.